2016
DOI: 10.1016/j.jbiomech.2016.03.047
|View full text |Cite
|
Sign up to set email alerts
|

How human gait responds to muscle impairment in total knee arthroplasty patients: Muscular compensations and articular perturbations

Abstract: Post-surgical muscle weakness is prevalent among patients who undergo total knee arthroplasty (TKA).We conducted a probabilistic multi-body dynamics (MBD) to determine whether and to what extent habitual gait patterns of TKA patients may accommodate strength deficits in lower extremity muscles. We analyzed muscular and articular compensations in response to various muscle impairments, and the minimum muscle strength requirements needed to preserve TKA gait patterns in its habitual status.Muscle weakness was si… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 46 publications
(7 reference statements)
0
9
1
Order By: Relevance
“…Considering that our body has a redundant number of muscles to execute a movement [Aoi et al, 2016;Valero-Cuevas et al, 2015], and muscles are apt to compensate for each other, thus masking abnormal activities in other muscles [Ardestani et al, 2016;Thompson et al, 2013;Goldberg et al, 2007], we believe that impaired neuro-motor synergies, caused by either surgery or osteoarthritis disease, may not immediately manifest themselves as abnormal EMG patterns.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Considering that our body has a redundant number of muscles to execute a movement [Aoi et al, 2016;Valero-Cuevas et al, 2015], and muscles are apt to compensate for each other, thus masking abnormal activities in other muscles [Ardestani et al, 2016;Thompson et al, 2013;Goldberg et al, 2007], we believe that impaired neuro-motor synergies, caused by either surgery or osteoarthritis disease, may not immediately manifest themselves as abnormal EMG patterns.…”
Section: Discussionmentioning
confidence: 99%
“…The remaining 13 TKA subjects with KFS < 5.5 were classified as the low-functional TKA group (8F/5M; age: 61.1±8.4 (year); BMI: 29.8±5.4 (kg/m 2 ), weight: 88.8±16.5 (kg)). KFS equal to 5.5 was chosen as the midpoint of KFS scale (0 to 10) and also based on our previous study demonstrating that 90% of patients with KFS >5.5 have stable knees which is an important factor in knee joint functionality [Ardestani et al, 2017]. To form a control group, we selected gait and EMG data from a database of unimpaired subjects who had no habitual pain and no history of fracture or surgery in the Downloaded for Anonymous User (n/a) at Indiana University -Ruth Lilly Medical Library from ClinicalKey.com by Elsevier on September 29, 2017.…”
Section: Subjectsmentioning
confidence: 99%
“…Our study observed that inadequate extension of operated knee at midstance phase was about 14°, which caused shorter stance phase of operated limb than nonoperated limb ( Table 2 ) and inadequate forward propulsion of body weight and further resulted in lower walking efficiency. Recent studies demonstrated that flexion of operated knee at stance phase was a core indicator that impacted the quality of gait [ 1 , 11 , 12 ], and knee flexion range in stance was the most important variable in discriminating between patients with TKA and controls [ 11 ].The study of Li et al [ 13 ] noted that this was mostly due to inadequate muscle strength of quadriceps femoris and motor control disorder as well as lower moment of force during knee extension.…”
Section: Discussionmentioning
confidence: 99%
“…The model showed acceptable accuracy in predicting muscle activations and the knee joint contact forces when compared versus in-vivo measurements (Chen et al, 2014;Peng et al, 2018). This model was also used for a series of parametric and probabilistic studies (Ardestani and Moazen, 2016;Chen et al, 2015). Here, this model was used to simulate muscle weakness (strength decline) and ligament laxity (decline in ligament force parameter) and calculate the resultant knee joint kinematics and kinetics.…”
Section: Musculoskeletal Modelmentioning
confidence: 99%
“…From each patient-specific model, 400 versions were generated including (i) 100 BSL models, for which muscle strength and ligament force parameter were chosen from a normal distribution of the nominal values for that subject ±5% (Amiri and Wilson, 2012) , (ii) 100 WEAK models where F0 was chosen from a normal distribution of nominal strength reduced by 30% (Silva et al, 2003). Note our previous study showed reduction beyond 40% can alter the normal gait pattern (Ardestani and Moazen, 2016); (iii) 100 WEAK models with lax ligaments where S0 was chosen from normal distribution of nominal values reduced by 30%. This is consistent with previous literature reporting up to 30% of variation in ligament stiffness amongst TKA subjects with unstable knees (Reinders et al, 2014) which may in turn lead to 2 standard deviation in secondary knee joint kinematics from the average (Kang et al, 2017).…”
Section: Musculoskeletal Modelmentioning
confidence: 99%